Influencing factors and countermeasures of training willingness of high-quality farmers in Jiangxi, China - Cheng, Sendi; Kiong Wong, Swee; Khalid, Zanudin (Edelweiss Applied Science and Technology, 2024)
This paper studies the factors influencing the training willingness of high-quality farmers, which is of great significance to improve the training efficiency. Through face-to-face interviews with 18 farmer trainees and online surveys of 514 farmer trainees, It was found that training content, training service and farmers' perception of training policy had significant impact on training willingness. However, demographic factors such as gender, age, education level, Agricultural post and previous farm income had insignificance on training intention. On this basis, countermeasures and suggestions were put forward from three aspects to improve the training willingness of high-quality farmers. Through pre-training demand survey, precise training content was proposed. Optimizing the training service and improving the satisfaction of training service, and improving policies and systems to protect the interests of farmers participating in training can be meaningful to enhance the internal motivation of farmers to actively participate in education and training.